LAW ENFORCEMENT BY PAMONG PRAJA POLICE UNIT ON POLLUTION OF COW WASTE IN NGAWI REGENCY - R. Kurniawan Bagas Wicaksono (Surakarta Law and Society Journal, 2022)
This article aims to find out the law enforcement by the Pamong Praja Police Unit against environmental pollution that comes from the negative impacts caused by the management of livestock manure that is not managed properly. The type of research used is sociological juridical research. The data used are primary data and secondary data. Primary data were obtained from interviews with the Pamong Praja Police Unit. While secondary data consists of primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques using interview techniques and literature study. The data analysis used descriptive analytical techniques. The conclusion in this article shows that law enforcement against livestock waste pollution in Ngawi Regency can be carried out preventively and repressively. Preventive law enforcement against livestock waste pollution is carried out by means of supervision. The repressive action taken by the Pamong Praja Police Unit of Ngawi Regency, namely by coming directly to the location of the cattle farm after reports from local residents related to the contamination of cattle farm waste. Furthermore, the repressive law enforcement carried out by the Ngawi Regency Pamong Praja Police unit is to provide sanctions in the form of a warning. If after the warning, the entrepreneur still has not taken care of cattle waste management, then technically the operation is carried out by the Pamong Praja Police Unit assisted with other relevant agencies to carry out the closure or revocation of cattle farming operations. Keywords: Law enforcement, waste pollution, cattle farming.